THE STUDY OF TIMING RELATIONSHIPS WHICH ARISE WHEN USING A TELEVISION CCD CAMERA WATEC WAT-902H2 SUPREME IN ASTRONOMICAL INVESTIGATIONS - Dragomiretsky, V. V.; Ryabov, A. V.; Koshkin, N. I. (Одеські астрономічні публікації, 2016)
The present paper describes the study of timing relationships which arise when using an analogue CCD camera Watec WAT-902H2 Sup in astronomical investigations, particularly in time-domain measurements of LEO satellites which are fast-moving against stellar background.